2000
DOI: 10.2307/3285000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Proteases in the Skin Mucus of Atlantic Salmon (Salmo salar) Infected with the Salmon Louse (Lepeophtheirus salmonis) and in Whole-Body Louse Homogenate

Abstract: As part of an investigation of the biochemical interactions between the salmon louse Lepeophtheirus salmonis and Atlantic salmon Salmo salar, we characterized protease activity in the skin mucus of noninfected Atlantic salmon and Atlantic salmon infected with L. salmonis and in an L. salmonis whole-body homogenate. Zymography revealed that mucus from infected salmon contained a series of low-molecular-mass (17-22 kDa) serine proteases that were not present in the mucus of noninfected salmon. Based on molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…high levels of cortisol) is responsible for the lack of response of Atlantic salmon to L. salmonis [8,9]. The identification of trypsin and PGE 2 in the secretions of L. salmonis has given validity to this hypothesis [8,10,11]. Prostaglandin E 2 is a vasodilatory compound that inhibits several salmonid immune-related genes including interleukin-1b (IL-1b), cyclooxygenase-2 (COX-2), and major histocompatibility (MH) class I and II [12].…”
Section: Introductionmentioning
confidence: 93%
“…high levels of cortisol) is responsible for the lack of response of Atlantic salmon to L. salmonis [8,9]. The identification of trypsin and PGE 2 in the secretions of L. salmonis has given validity to this hypothesis [8,10,11]. Prostaglandin E 2 is a vasodilatory compound that inhibits several salmonid immune-related genes including interleukin-1b (IL-1b), cyclooxygenase-2 (COX-2), and major histocompatibility (MH) class I and II [12].…”
Section: Introductionmentioning
confidence: 93%
“…It is noteworthy that LMPs include domains with properties of trypsin and proteinase inhibitors. Lice release proteases that may be required for nutrition or immunomodulation and inactivation of protective proteins (Firth et al, 2000), and their neutralization can be beneficial for the host. Possible importance of mucus in the salmon-louse interaction is commonly recognized.…”
Section: E-bc T-bc C-3 E-3 T-3 C-16 E-16 T-16mentioning
confidence: 99%
“…The information available on a hostemucosalepathogen paradigm with respect to infection and disease susceptibility has been compelling enough to further characterize these components, primarily from the host mucus. Characterization of the mucus from fish skin has been approached from different angles, which includes the focus on the different proteases present in the skin mucus [7,8]. A study on cod skin mucus proteases has revealed that serine proteases are more predominant than metalloproteases and that overall protease activity was less compared to some fresh water fish and hag fish [9].…”
Section: Introductionmentioning
confidence: 99%